Maladaptive stress: Theoretical, neurobiological and clinical profiles - Giulio Perrotta (Archives of Depression and Anxiety - Peertechz Publications, 2021)
Stress is an adaptive response of the organism to an event that can be both internal and external, interfering at the endocrine, humoral, organic and biological levels: If the person reacts with all his resources, in a constructive and functional way, then we speak of "eustress", responding in an adaptive and functional way; if, on the other hand, the person fails to draw on his strategies, then we speak of "distress", giving rise to a more or less pervasive and serious form of maladaptation, which if reinforced with specific conditioning could give rise to one or more psychopathologies. It is therefore important to intervene on the person, according to a precise therapeutic plan, and on his mental and personality patterns, in order to remodel certain learned models that reinforce maladaptation and to support and assist the person in his process of awareness towards the invalidating and/or dysfunctional condition.